Starch/chitosan films reinforced with polydopamine modified MMT: Effects of dopamine concentration. (December 2016) - Zhou, Min; Liu, Qin; Wu, Shuaishuai; Gou, Zhenqiong; Wu, Xiyu; Xu, Dan
Abstract: Montmorillonite (MMT) was modified by bio-inspired polydopamine (PDA), which is the self-polymerized product of dopamine (DA), to improve the dispersion property of MMT in polymer matrix. As revealed by FTIR spectra, XRD profiles and SEM micrographs, PDA has been successfully coated onto MMT surface thus enlarge the interlayer spacing, resulting PDA modified MMT (MMT-Dx). The lamellar structure of MMT-Dx was found to be highly related to the DA concentration applied during the modification process. The exfoliation degree of MMT-Dx increased along with the weight content of PDA coating, as the DA concentration increased from 0.5 mg/mL to 3 mg/mL. MMT-Dx was then incorporated into starch/chitosan (ST/CS) blended matrix at a loading level of 2 wt% to reinforce the bio-polymers. Compared to neat MMT, MMT-Dx showed much higher dispersion capability as observed from XRD profiles and SEM micrographs. Furthermore, as DA concentration increased, the tensile strength and Young's modulus of the composite films increased. The composite film containing MMT-Dx modified by 3 mg/mL DA displayed a tensile strength as high as 30.44 MPa and a Young's modulus as high as 1.42 GPa, which were 2.1 and 1.6 times the values of the neat ST/CS film, respectively. Therefore, to adopt PDA modification, MMT-Dx with adjustable interlayer spacing and different dispersion properties can be obtained, which provide multiple choices of nano-fillers for bio-polymers reinforcement; thus accelerate the acceptances of these bio-polymers in food packaging and related applications. Graphical abstract: Highlights: MMT was modified by polydopamine using different initial dopamine concentration. Modified MMT (MMT-Dx) showed different lamellae structure and dispersibility. MMT-Dx can better reinforce starch/chitosan composite films compared to neat MMT.